Maternal and neonatal outcome in premature rupture of membranes: a retrospective study - Rajakumar, Shery Angel; Myneni, Sindhura; Samuel, Ajay Nickson (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Premature rupture of membranes (PROM) is one of the most challenging and controversial obstetric dilemma which occur even in low risk pregnancies. This study was done to analyse the maternal and neonatal outcomes in PROM cases. Methods: This was a retrospective study conducted in the department of Obstetrics and Gynaecology at Chettinad Hospital and Research Institute, during a period of 3 years from August 2017 to August 2020. All the women who admitted with PROM were included in the study. The data regarding parity, gestational age, number of fetuses, presentation, duration of PROM, PROM to delivery interval, mode of delivery, weight of the baby, NICU admission was collected from the hospital records and analysed. Results: A total of 115 cases of PROM were recorded. High incidence is found in the age group of 20-30 years. Among them 73.04% were admitted at term. 71.3% were primigravida. 58.26% of them delivered vaginally where as 41.74% delivered by LSCS. Majority of them admitted within 6 hours of PROM. Majority of them delivered within 12 hours of PROM. High APGAR scores in majority of the cases. Most of the babies had birth weight >2.5 kg. 16 babies were admitted in NICU. There was no maternal mortality in our study though we had one neonatal mortality. Conclusions: Careful identification of present or impending complications and individualizing the management based on gestational age and presence of complications holds good in optimising fetomaternal outcome in PROM.